2017
DOI: 10.1016/j.pjnns.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Association between C677T polymorphism of MTHFR gene and risk of amyotrophic lateral sclerosis: Polish population study and a meta-analysis

Abstract: Although we did not find the association between C677T polymorphism of MTHRF gene and risk of ALS in Polish population, the results of meta-analysis suggest that the TT genotype can be a genetic risk factor for ALS in Caucasian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The basic features of the 25 case-control studies ( Nakata et al, 1998 ; Zheng et al, 2000 ; Yingdong et al, 2002 ; Li et al, 2003 ; Zhang et al, 2004 ; Yan et al, 2004 ; Fang and Wu, 2004 ; Ye et al, 2004 ; Żur-Wyrozumska et al, 2017 ; Fang et al, 2005 ; Dikmen et al, 2006 ; Sazci et al, 2006 ; Hu et al, 2007 ; Shen et al, 2007 ; Zhang et al, 2008 ; Ruigrok et al, 2010 ; Hultdin et al, 2011 ; Somarajan et al, 2011 ; Atadzhanov et al, 2013 ; Rui-Rui et al, 2013 ; Das et al, 2015 ; Shao et al, 2016 ; Hu et al, 2016 ; Abidi et al, 2018 ; Jiang et al, 2018 ) included are shown in Table 1 . The incorporated studies ranged from 1998 to 2018, involving mainly Asian populations and some European and African communities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The basic features of the 25 case-control studies ( Nakata et al, 1998 ; Zheng et al, 2000 ; Yingdong et al, 2002 ; Li et al, 2003 ; Zhang et al, 2004 ; Yan et al, 2004 ; Fang and Wu, 2004 ; Ye et al, 2004 ; Żur-Wyrozumska et al, 2017 ; Fang et al, 2005 ; Dikmen et al, 2006 ; Sazci et al, 2006 ; Hu et al, 2007 ; Shen et al, 2007 ; Zhang et al, 2008 ; Ruigrok et al, 2010 ; Hultdin et al, 2011 ; Somarajan et al, 2011 ; Atadzhanov et al, 2013 ; Rui-Rui et al, 2013 ; Das et al, 2015 ; Shao et al, 2016 ; Hu et al, 2016 ; Abidi et al, 2018 ; Jiang et al, 2018 ) included are shown in Table 1 . The incorporated studies ranged from 1998 to 2018, involving mainly Asian populations and some European and African communities.…”
Section: Resultsmentioning
confidence: 99%
“…The incorporated studies ranged from 1998 to 2018, involving mainly Asian populations and some European and African communities. Three different races were involved in these 25 selected studies: two ( Atadzhanov et al, 2013 ; Abidi et al, 2018 ) African, three ( Dikmen et al, 2006 ; Sazci et al, 2006 ; Hultdin et al, 2011 ) Caucasian and the remaining 17 ( Nakata et al, 1998 ; Zheng et al, 2000 ; Yingdong et al, 2002 ; Zhang et al, 2004 ; Yan et al, 2004 ; Fang and Wu, 2004 ; Ye et al, 2004 ; Żur-Wyrozumska et al, 2017 ; Hu et al, 2007 ; Zhang et al, 2008 ; Rui-Rui et al, 2013 ; Shao et al, 2016 ; Hu et al, 2016 ; Jiang et al, 2018 ) Asian. The control population in three of the 25 studies ( Li et al, 2003 ; Shen et al, 2007 ; Das et al, 2015 ) did not meet Hardy-Weinberg equilibrium and be excluded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a study performed in an Italian population failed to show an association between the C677T polymorphism and the risk of ALS [105]. A recent meta-analysis suggested that the TT polymorphism could be a genetic risk for sporadic ALS in the Caucasian population [106]. If the association between hyperhomocysteinemia and ALS is proven to be causal, then reducing the levels of Hcy could potentially reduce the incidence of ALS.…”
Section: Abnormal Metabolism Of Saas In Alsmentioning
confidence: 99%
“…Variation in genes involved in the folate pathway has been suggested as a possible factor implicated in ALS since this vitamin is essential to DNA synthesis and homocysteine (Hcy) metabolism, the dysregulation folate metabolism unbalances the cellular homeostasis, and could contribute to neurodegenerative processes in motor neurons [16,17]. The Methylenetetrahydrofolate reductase (MTHFR) gene stands out as a potential target, considering that it is responsible for encoding the MTHFR enzyme, which plays a crucial role in intracellular folate metabolism [18].…”
Section: Introductionmentioning
confidence: 99%